2004
DOI: 10.1038/ng1356
|View full text |Cite|
|
Sign up to set email alerts
|

Long lifespan in worms with long telomeric DNA

Abstract: Telomere length is a crucial factor in senescence 1-3 , but it has not been determined whether animals with long telomeres live longer than those with normal-length telomeres in the isogenic background of a given species. Here we show the effect of long telomeres on lifespan in the nematode Caenorhabditis elegans. We examined the effect of telomere length on lifespan by overexpressing HRP-1, a telomere-binding protein, which gradually increased telomere length in worms. Worms with longer telomeres lived longer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 27 publications
9
91
1
1
Order By: Relevance
“…It is a formal possibility that the association between stress and telomere length reported here is in part due to people with longer telomeres being psychologically more resistant to objective stressors than people with shorter telomeres. Engineering worms to have longer telomeres resulted in an extension of their life spans, even though all of their somatic cells are postmitotic and their telomeres do not shorten during aging (25). Further, the biochemical pathway involved in this effect of telomere length on life span is the same pathway previously shown to mediate increased physiological stress resistance in response to various genetic variants that increase life span.…”
Section: Discussionmentioning
confidence: 74%
“…It is a formal possibility that the association between stress and telomere length reported here is in part due to people with longer telomeres being psychologically more resistant to objective stressors than people with shorter telomeres. Engineering worms to have longer telomeres resulted in an extension of their life spans, even though all of their somatic cells are postmitotic and their telomeres do not shorten during aging (25). Further, the biochemical pathway involved in this effect of telomere length on life span is the same pathway previously shown to mediate increased physiological stress resistance in response to various genetic variants that increase life span.…”
Section: Discussionmentioning
confidence: 74%
“…In another role that is likely significant in cancer, human A1 has been implicated in lengthening and maintaining telomeres, a function that is conserved in C. elegans and possibly yeast (Lin and Zakian 1994;LaBranche et al 1998;Joeng et al 2004). A1 binds to the single-stranded telomeric DNA repeat sequence TAGGGT (a sequence almost identical to the high-affinity SELEXbinding site identified for A1 using RNA), where it is capable of stimulating telomerase activity (Burd and Dreyfuss 1994;Zhang et al 2006).…”
Section: Hnrnp and Sr Proteins In Proliferation And Cancermentioning
confidence: 99%
“…Telomerase-based strategies"). The results in the nematode Caenorhabditis elegans suggest that signaling may be initiated in postmitotic somatic cells by TL to regulate organismal life span [54]. There is an evidence linking TL and survival [55].…”
Section: Molecular Biologics Of Telomeredependent Senescencementioning
confidence: 99%
“…Studies in a range of organisms have shown that telomeres shorten with age in various somatic tissues [47][48][49][50][51][52][54][55][56], and individuals with relatively long telomeres have a greater life expectancy than those with short telomeres [40,52,[54][55][56][57][58]. However, such an effect could be a consequence of either an initially long TL or a slow rate of telomere erosion.…”
Section: Molecular Biologics Of Telomeredependent Senescencementioning
confidence: 99%